Hubungan Asupan Lemak Total Dan Asupan Kolesterol Dengan Kadar Kolesterol Darah Pada Lansia Di Posyandu Aisyiyah Kota Surakarta - Sukma Dewandaru, Elitha, dr. Listiana Dharmawati S, M.Si, Ahmad Farudin, SKM, M.Si (2015)
Introduction: The composition of food that contain high calories and fat can lead to increasing blood cholesterol level in the elderly. Once the increase of cholesterol in the blood are ignored, it can accelerate atherosclerosis. Purpose: This research aims to understand the relationship between Total Fat, Cholesterol Intake and Blood Cholesterol Level in Elderly in Integrated Helath Service Aisyiyah of Surakarta Research method: This research included observational research with the crossectional. Sampling method used was Consecutive sampling. Data method of were collected by recall 3x24hour and electrode-based biosensor. Results: Research respondents had high cholesterol levels as much as 97,6% with normal total fat 51,4% and cholesterol intake as much as 97,5%. Spearman test result showed that there is no significant relationship between Total Fat Intake and Blood Cholesterol Level (p =0,393), and there is no significant relationship between Cholesterol Intake and Blood Cholesterol Level in Elderly in Integrated Helath Pos Aisyiyah of Surakarta (p=0,903). Conclusion: There is no significant relationship between Total Fat Intake and Cholesterol Intake with Blood Cholesterol Level in Elderly in Integrated Helath Pos Aisyiyah of Surakarta